A Framework for Understanding the Role of Psychological Processes in Disease Development, Maintenance, and Treatment: The 3P-Disease Model - Wright, Casey D.; Tiani, Alaina G.; Billingsley, Amber L.; Steinman, Shari A.; Larkin, Kevin T.; McNeil, Daniel W. (Frontiers in Psychology, 2019)
Health psychology is multidisciplinary, with researchers, practitioners, and policy makers finding themselves needing at least some level of competency in a variety of areas from psychology to physiology, public health, and others. Given this multidisciplinary ontology, prior attempts have been made to establish a framework for understanding the role of biological, psychological, and socio-environmental constructs in disease development, maintenance, and treatment. Other models, however, do not explain how factors may interact and develop over time. The aim here was to apply and adapt the 3P model, originally developed and used in the treatment of insomnia, to couch the biopsychosocial model in a way that explains how diseases develop, are maintained, and can be treated. This paper outlines the role of predisposing, precipitating, and perpetuating factors in disease states and conditions (the 3Ps) and provides examples of how this model may be adapted and applied to a number of health-related diseases or disorders including chronic pain, heart disease, gastrointestinal disorders, and oral disease. The 3P framework can aid in facilitating a multidisciplinary, theoretical approach and way of conceptualizing the study and treatment of diseases in the future.